Knowledge and Assertion in Korean. (11th July 2018) - Turri, John; Park, YeounJun
Abstract: Evidence from life science, cognitive science, and philosophy supports the hypothesis that knowledge is a central norm of the human practice of assertion. However, to date, the experimental evidence supporting this hypothesis is limited to American anglophones. If the hypothesis is correct, then such findings will not be limited to one language or culture. Instead, we should find a strong connection between knowledge and assertability across human languages and cultures. To begin testing this prediction, we conducted three experiments on Koreans in Korean. In each case, the findings replicated prior results observed in Americans and were corroborated by key findings from new replication studies on Americans using materials back‐translated from Korean. These findings support the theory that there is a core, cross‐culturally robust human practice of assertion and that, according to the rules of this practice, assertions should express knowledge.